INFLUENCE OF WHEELED TYPES OF A Skidder ON PRODUCTIVITY AND COST OF THE FOREST HARVESTING - Lopes, Eduardo Silva; Oliveira, Diego de; Sampietro, Jean Alberto (Floresta, 2013)
Abstract The objective of this study was to evaluate the influence of different wheel types of a skidder on productivity and cost of Pinus taeda L. wood extraction. The study was conducted in a forestry company located in the municipality of Mandirituba, Paraná state, Brazil. The technical and cost analyses included a time and motion study of the wood extraction activity. The productivity, operative efficiency, energy consumption and the production and operational costs were determined for the machines with different wheel types: SDP - skidder with rubber tires; SD2 – skidder with tracks on the two front tires; and SD4 – skidder with tracks on the four tires. Results showed that the activity that demanded most time in the operational cycle was the maneuvering of the machines to pick up more than one tree, resulting in lost of productivity and need of improvement in the operational planning. The skidder equipped only with rubber tires showed higher productivity and lower production cost in the longest extraction distances, caused by the higher operating speed of the machine. Keywords: Timber extraction; wheel types; operating efficiency. Resumo Influência dos rodados de um skidder na produtividade e no custo da extração florestal. Este trabalho objetivou avaliar a influência de diferentes tipos de rodados de um skidder na produtividade e no custo da extração de madeira de Pinus taeda L. O estudo foi conduzido em uma empresa florestal localizada no município de Mandirituba, estado do Paraná, Brasil. As análises técnica e de custo englobaram um estudo de tempos e movimentos da operação de extração florestal. Foi determinado a produtividade, eficiência operacional, rendimento energético e custos operacionais e de produção das máquinas equipadas com diferentes tipos de rodados: SDP – skidder com rodados de pneus; SD2 – skidder com pneus dianteiros recobertos com semiesteiras e SD4 – skidder com os quatro pneus recobertos com semiesteiras. Os resultados mostraram que a atividade que demandou o maior tempo do ciclo operacional foram as manobras realizadas pelas máquinas para apanhar mais de uma árvore, ocasionando perda de produtividade e necessidade de melhoria no planejamento operacional. O skidder equipado somente com rodados de pneus apresentou maior produtividade e menor custo de produção nas maiores distâncias de extração, ocasionado pela maior velocidade operacional da máquina. Palavras-chave: Extração florestal; tipos de rodados; eficiência operacional.